Temperature‐Tunable Terahertz Perfect Absorber Based on All‐Dielectric Strontium Titanate (STO) Resonator Structure. Issue 12 (23rd September 2022) - Zhao, Jingcheng; Cheng, Yongzhi
Abstract: A temperature‐tunable terahertz (THz) perfect absorber (PA) composed of a periodic array of deep subwavelength micro‐cross‐shaped (MCS) structures of the strontium titanate (STO) resonator is proposed and investigated theoretically, which can be applicable for the temperature sensing. Simulation results indicate that the absorbance of 99.8% at 0.221 THz can be achieved when the designed PA is under the room temperature of T = 300 K, which is in good agreement with the calculation done by the coupling mode theory (CMT). The simulated distributions of electric and magnetic fields in the unit‐cell structure of the designed PA reveal that the observed perfect absorption is mainly attributed to the Mie resonance of the all‐dielectric MCS structure STO. In addition, this designed PA is polarization‐insensitive and wide‐angle absorption for both transverse magnetic (TM) and transverse electric (TE) waves. The resonance absorption properties of the designed PA can be controlled by changing the geometrical parameters of STO resonator structure. The designed PA can be served as a temperature sensor, which has a sensitivity of about 0.37 GHz K −1 since the electrical property of the STO is dependent on the variation of surrounding temperature. Furthermore, the perfect absorption can also be achieved by the PAs using the square, circular, and ring STO structures. The proposed design concepts of the STO‐based tunable PAs can find potential THz applications in sensing, detecting, imaging, and so on. Abstract : A tunable terahertz (THz) perfect absorber (PA) composed of deep subwavelength cross‐shaped strontium titanate (STO) is proposed, and an absorbance of 99.8% at 0.221 THz can be achieved under room temperature, 300 K. The designed PA has a sensitivity of about 0.37 GHz K −1 . Furthermore, the perfect absorption can also be achieved by using the square, circular, and ring‐shaped STO structures.